Role of SNARE-dependant gliotransmitter release by astrocytes on the modulation of synaptic plasticity by BDNF - Jesus, João Pedro de Almeida, 1993- (2020)
Tese de mestrado, Neurociências, Universidade de Lisboa, Faculdade de Medicina, 2017